Controlling System of Automatic Microcontroller for Passion Fruit Juice Extractor - Sidehabi, Sitti Wetenriajeng; Mutmainnah; Saiful Ashar (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The fruits are squeezed to extract their concentrate in fruit processing factories or industries, especially for the purple passion fruit variety. However, separating seeds from the fruit pulp uses a blender, resulting in a mixture of seeds and pulp. In this industry, seeds and fruit pulp are separated using a spinner machine and operated manually by operators. So, adding an automatic mechanism has the potential for optimization and improvement. This research aims to develop a passion fruit squeezing machine with maintenance and automation, upgrading the passion fruit filtering and squeezing spinner machine. The purpose is to control the speed of the passion fruit filtering motor using an AC Dimmer module and create an efficient automated tool for the passion fruit mixer and extractor machine. A squeezing machine is designed by utilizing a counter module to count the incoming passion fruits into the cylinder, and an Arduino Uno is used as the controller to adjust the motor speed using an AC dimmer. The passion fruit filtering machine is operated at a minimum triggering angle of 130 degrees and a maximum triggering angle of 80 degrees, or voltages ranging from 69.9 V to 102 V, with a minimum speed of 780 RPM and a total rate of 1462 RPM, and the squeezing time varies from 2 to 4 minutes.